Ritual Upa Upa Tondi Mandailing: Jejak Kultural dan Kritik Teologis Islam - Bais, Abdul; Abbas, Mardhiah (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
Upa Upa Tondi is a cultural tradition that is still preserved by Mandailing ethnic communities, but its suitability with Islamic aqidah needs to be reviewed. This tradition is believed to contain elements of spiritual support, but potentially contains values that are contrary to the principle of tawhid. The purpose of this study is to examine the meaning and implementation of the tradition and critically analyze it from the perspective of Islamic aqidah in order to find a balance point between cultural preservation and purity of faith. The research uses a qualitative method with a social theology approach, collecting data through observation and interviews with traditional and religious figures. The findings show that this tradition contains positive social values such as solidarity, empathy, and communal care. However, from an Islamic theological perspective, this practice requires critical evaluation to ensure it does not deviate from the principle of tawhid, especially regarding beliefs in spiritual elements not based on Islamic teachings. Therefore, a wise and educational approach is needed so that this tradition can continue to be preserved within the framework of pure Islamic values.